독도 물골 지하유출수의 수문학적 특성 - 우남칠(Nam C. Woo); 이동엽(Dong Y. Lee); 박종훈(Jong H. Park); 김윤배(Yoon B. Kim); 우민수(Min S. Woo); 박찬홍(Chan H. Park) (자원환경지질, 2022)
Whether Dokdo can sustain human habitation or economic life of their own plays an important role to the legal status of the island in the international maritime law. This study reports the hydrological survey results regarding the water resource of the island occurred at Moolgol in Seodo. The amount of underground discharge at Moolgol was estimated at least 1.1 m3/d, conforming the results of previous studies. Based on the oxygen and hydrogen isotope ratios of water, the discharge appeared to originate from precipitation, and about 36% of the daily precipitation moves fast to the Moolgol through the joints developed in the volcanic bedrocks. Quality of the discharged water shows relatively higher concentrations in Cl and NO3 to be used for drinking and domestic purposes, probably affected by the sea spray and waves from surrounding sea and the birds' excretion such as black-tailed gulls. 독도에서의 "인간의 거주 혹은 독자적인 경제활동을 영위할 수 있는가의 여부"는 국제법 상으로 독도의 지위를 결정하는 중요한 요소로 작용한다. 이러한 관점에서 독도의 활용가능한 물(water resource)에 대하여, 독도에서 유일하게 지하수 유출이 발생하고 있는 서도의 물골을 대상으로 조사한 수문학적 결과를 보고한다. 이 조사에서 평가한 물골의 지하수 유출량은 최소 1.1 m3/d로 나타났으며, 이는 기존의 연구들에서 제시한 결과와 통계적으로 유사하다. 물의 산소-수소 안정동위원소비를 통한 기원 분석에서 지하유출수의 기원은 강수로 판단되며, 일강수량을 기준으로 할 때, 강수의 약 36% 정도는 화산암 내의 절리를 통해 빠르게 지하수로 유출된다. 지하유출수의 수질은 생활용수와 음용수로 사용하기에는 높은 염도와 질산염 농도를 보이며, 이들은 해무와 파도 등에 의한 염분과 괭이 갈매기 등 조류 배설물로부터 기인된 것으로 판단된다.